The antiepileptic and anticancer agent, valproic acid, induces P-glycoprotein in human tumour cell lines and in rat liver - Eyal, S (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: The antiepileptic drug valproic acid, a histone deacetylase (HDAC) inhibitor, is currently being tested as an anticancer agent. However, HDAC inhibitors may interact with anticancer drugs through induction of P-glycoprotein (P-gp, MDR1) expression. In this study we assessed whether valproic acid induces P-gp function in tumour cells. We also investigated effects of valproic acid on the mRNA for P-gp and the cytochrome P450, CYP3A, in rat livers. >EXPERIMENTAL APPROACH: Effects of valproic acid on P-gp were assessed in three tumour cell lines, SW620, KG1a and H4IIE. Accumulation of acetylated histone H3 in rats' livers treated for two or seven days with valproic acid was evaluated using a specific antibody. Hepatic expression of the P-gp genes, mdr1a, mdr1b and mdr2, was determined by real-time polymerase chain reaction. The effects of valproic acid on CYP3A were assessed by Northern blot analysis and CYP3A activity assays. KEY RESULTS: Valproic acid (0.5–2.0 mM) induced P-gp expression and function up to 4-fold in vitro. The effect of a series of valproic acid derivatives on P-gp expression in SW620 and KG1a cells correlated with their HDAC inhibition potencies. Treatment of rats with 1 mmol kg(−1) valproic acid for two and seven days increased hepatic histone acetylation (1.3- and 3.5-fold, respectively) and the expression of mdr1a and mdr2 (2.2–4.1-fold). Valpromide (0.5–2.0 mM) did not increase histone acetylation or P-gp expression in rat livers, but induced CYP3A expression. CONCLUSIONS: Valproic acid increased P-gp expression and function in human tumour cell lines and in rat liver. The clinical significance of this increase merits further investigation.